Postural fatigue of the shoulder: relationships between maximum endurance, subjective perception and electromyographic responses - Serratos Pérez, J. Nieves (1994)
The present study was undertaken to investigate issues concerned with the endurance to muscular loads created by the holding of static postures, without the presence of any other form of muscular effort. Its main aim was to explore the possibilities for the development of models which are expected to account for the capacity to endure such kind of exertion.